STRATEGI PEMASARAN PRODUK SIMPANAN BRI BRITAMA JUNIO DALAM MENGHIMPUN DANA MASYARAKAT PADA PT. BANK RAKYAT INDONESIA (PERSERO) TBK KANTOR CABANG BINTARO - Hadi Purwanto (ITB Swadharma, 2020)
The growing banking sector and the presence of various products and services offered by other banks to satisfy and meet customer needs have encouraged BRI to always innovate on its products and services. This makes PT. BRI (Persero) Tbk Bintaro Branch seeks to develop various marketing strategies to attract and retain customers. The BRI BritAma Junio savings account is a tool that can attract the attention of child customers as well as parents to get in touch with BRI Bank. Increasing competition between banks in consumer banking, especially competition for meeting individual needs with a large number of diversification of deposit products, Bank BRI needs to develop products and create appropriate sales programs for customers. Diversification of savings products is the right strategy to seize market share, especially in the urban market, because the characteristics of the urban market tend to have many desires